If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2n + -4)(3n + -6) = 0 Reorder the terms: (-4 + 2n)(3n + -6) = 0 Reorder the terms: (-4 + 2n)(-6 + 3n) = 0 Multiply (-4 + 2n) * (-6 + 3n) (-4(-6 + 3n) + 2n * (-6 + 3n)) = 0 ((-6 * -4 + 3n * -4) + 2n * (-6 + 3n)) = 0 ((24 + -12n) + 2n * (-6 + 3n)) = 0 (24 + -12n + (-6 * 2n + 3n * 2n)) = 0 (24 + -12n + (-12n + 6n2)) = 0 Combine like terms: -12n + -12n = -24n (24 + -24n + 6n2) = 0 Solving 24 + -24n + 6n2 = 0 Solving for variable 'n'. Factor out the Greatest Common Factor (GCF), '6'. 6(4 + -4n + n2) = 0 Factor a trinomial. 6((2 + -1n)(2 + -1n)) = 0 Ignore the factor 6.Subproblem 1
Set the factor '(2 + -1n)' equal to zero and attempt to solve: Simplifying 2 + -1n = 0 Solving 2 + -1n = 0 Move all terms containing n to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1n = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -1n = 0 + -2 -1n = 0 + -2 Combine like terms: 0 + -2 = -2 -1n = -2 Divide each side by '-1'. n = 2 Simplifying n = 2Subproblem 2
Set the factor '(2 + -1n)' equal to zero and attempt to solve: Simplifying 2 + -1n = 0 Solving 2 + -1n = 0 Move all terms containing n to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1n = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -1n = 0 + -2 -1n = 0 + -2 Combine like terms: 0 + -2 = -2 -1n = -2 Divide each side by '-1'. n = 2 Simplifying n = 2Solution
n = {2, 2}
| y-1.1=-1.2 | | 10=f/3 | | x+20=43 | | X+21+2x=12-2x-17 | | 20/x-5=-8/6 | | 3+10=s | | -9a=72 | | .09x=5 | | 4y+u+35=180 | | 12x+5=-2x+19 | | .09x=10 | | 2/9v=14 | | .09x=15 | | -x^3+1.5x^2-.5x=0 | | -x^3+1.5x^2-04x=0 | | 3+10=5 | | A=(1/2)bb | | 2cos^2(x)+9cos(x)=0 | | 3y+8=2y-8 | | -3x+9=3+4x+(-7x)+6 | | 4y=y+35 | | 4000*4.254= | | B/3=-27 | | M-1/6=5/6 | | -6(8x+15)=390 | | -10+-8m=-110+6m | | g(x)=-6x-7 | | -7(6x+2)=-266 | | 7x+2=5x+(-2) | | 6(-9x+5)=-240 | | 7(x)-2=26 | | -6(-6x-10)=276 |